Provider Attitudes and Practices on Treating Tobacco Dependence in New York City After 10 years of Comprehensive Tobacco Control Efforts - Elizabeth A. Kilgore; Elizabeth Needham Waddell; Kathryn M. Tannert Niang; Jennifer Murphy; Sayone Thihalolipavan; Shadi Chamany (SAGE Publishing, 2021)
To design strategies for provider education and implementation of clinical guidelines, this study investigated how physicians (1) approach tobacco cessation, including barriers to screening and treatment, (2) prioritize tobacco cessation, and (3) perceive the role of public health. Semi-structured focus groups were conducted with 30 New York City physicians across specialties. Physicians reported that they: (1) understand risks of smoking, as well as basic counseling and medications for smoking cessation; (2) do not always follow clinical guidelines for treatment of smoking cessation; (3) prioritize treatment of patients based upon a number of criteria; and (4) see the role of public health and the city health department as separate from the clinical environment, despite population-level interventions to reduce smoking. Physicians understand the importance of treating tobacco dependence, but identified barriers to treatment, some of which are health system-related. Further, patients who do not yet present with smoking-related illness may receive less intense interventions.